Comparative Genomic Analysis of slc39a12/ZIP12: Insight into a Zinc Transporter Required for Vertebrate Nervous System Development - Chowanadisai, Winyoo (PLoS One, 2014)
The zinc transporter ZIP12, which is encoded by the gene slc39a12, has previously been shown to be important for neuronal differentiation in mouse Neuro-2a neuroblastoma cells and primary mouse neurons and necessary for neurulation during Xenopus tropicalis embryogenesis. However, relatively little is known about the biochemical properties, cellular regulation, or the physiological role of this gene. The hypothesis that ZIP12 is a zinc transporter important for nervous system function and development guided a comparative genetics approach to uncover the presence of ZIP12 in various genomes and identify conserved sequences and expression patterns associated with ZIP12. Ortholog detection of slc39a12 was conducted with reciprocal BLAST hits with the amino acid sequence of human ZIP12 in comparison to the human paralog ZIP4 and conserved local synteny between genomes. ZIP12 is present in the genomes of almost all vertebrates examined, from humans and other mammals to most teleost fish. However, ZIP12 appears to be absent from the zebrafish genome. The discrimination of ZIP12 compared to ZIP4 was unsuccessful or inconclusive in other invertebrate chordates and deuterostomes. Splice variation, due to the inclusion or exclusion of a conserved exon, is present in humans, rats, and cows and likely has biological significance. ZIP12 also possesses many putative di-leucine and tyrosine motifs often associated with intracellular trafficking, which may control cellular zinc uptake activity through the localization of ZIP12 within the cell. These findings highlight multiple aspects of ZIP12 at the biochemical, cellular, and physiological levels with likely biological significance. ZIP12 appears to have conserved function as a zinc uptake transporter in vertebrate nervous system development. Consequently, the role of ZIP12 may be an important link to reported congenital malformations in numerous animal models and humans that are caused by zinc deficiency.